Livelihood vulnerability to drought: A case of rural Iran. (March 2017) - Keshavarz, Marzieh; Maleksaeidi, Hamideh; Karami, Ezatollah
Abstract: Agriculture as the main source of livelihood for rural residents of the developing countries is inherently sensitive to climate variability and change. Among different climatic events, drought is frequently identified as a major threat to agricultural systems and livelihood security of farm families, in many arid and semi-arid regions of the developing world. The negative impacts of drought are further intensified by the threat of climate change. In order to mitigate the negative impacts of drought on livelihood, increasing adaptive capacity of farm families is imperative. If rural livelihoods are no longer secure, farm families are finally forced to abandon agriculture. Therefore, the objective of this study was to investigate the livelihood vulnerability of farm families to drought. It was also intended to determine the drivers of livelihood vulnerability in the context of drought. A survey of 274 farm families of Fars province, selected through a multistage stratified random sampling technique, indicated that drought is the main threat to livelihood security meantime the interaction between drought intensity and its duration leads to more vulnerability. Additionally, results revealed that different adaptation strategies were used by the low, medium and high livelihood vulnerable families in order to adjust drought impacts. Tree analysis also illustrated that livelihood vulnerability is a product of the complex set of financial, physical, social and natural capitals. Some recommendations are offered to reduce the livelihood vulnerability of farm families to drought. Highlights: Drought is a major threat to agricultural systems and rural livelihood security. If livelihood is no longer secure, farm families are forced to abandon agriculture. Farm families' livelihood vulnerability was induced by a complex set of factors. Different levels of vulnerability, i.e. low, medium and high, were determined. Different significant adaptation strategies were used by vulnerable categories.